2018
DOI: 10.1111/tran.12240
|View full text |Cite
|
Sign up to set email alerts
|

Transitional organisations, affective atmospheres and new forms of being‐in‐common: Post‐disaster recovery in Christchurch, New Zealand

Abstract: With reference to the post-disaster urban landscape of Christchurch, New Zealand, this paper examines the emergence of particular forms of nongovernmental organisation after the 2010 and 2011 earthquakes, and the kinds of transitional activities in which they have been engaged. Two sets of conceptual apparatus are deployed. First, we suggest that the spaces and activities of transitional organisations have provoked particular "affective atmospheres" in Christchurch that are informing new senses of place, belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…So, for example, Breul and Revilla Diez (2018) in their study of a global production network restrict direct quotation to short snippets of interview text. Kivelä (2018) uses short quotes – again from experts – to back up analytical statements about the relationship between citizenship and health care provision in Finland (see also Hall, 2015; Cloke and Conradson, 2018). A similar effect, although created this time with more substantial interview quotes, is evident in Poon et al’s (2018) study of Sharia finance in Malaysia.…”
Section: Current Quotation Culturesmentioning
confidence: 99%
“…So, for example, Breul and Revilla Diez (2018) in their study of a global production network restrict direct quotation to short snippets of interview text. Kivelä (2018) uses short quotes – again from experts – to back up analytical statements about the relationship between citizenship and health care provision in Finland (see also Hall, 2015; Cloke and Conradson, 2018). A similar effect, although created this time with more substantial interview quotes, is evident in Poon et al’s (2018) study of Sharia finance in Malaysia.…”
Section: Current Quotation Culturesmentioning
confidence: 99%
“…Yet many of these organisations have applied for funding from local and central government and have worked alongside council and government departments to achieve their aims. This has been one critique of these projects, presented as evidence of the neoliberal co‐option of the initiatives (Cloke and Conradson ). More broadly, some scholars have also suggested that temporary urbanism through transitional projects are seductive concepts that utilise experimental approaches to push the boundaries of urban projects while not challenging the foundations of “neoliberal urban development” (Ferreri :183).…”
Section: A Diverse Politics Of Disaster Recoverymentioning
confidence: 99%
“…As Till and McArdle () note, when framed as “temporary projects” officials readily see these projects as “stop gaps” that further capital accumulation and contribute to gentrification, yet in practice these projects support non‐capitalist forms of exchange and create space for alternative urban imaginaries. In the case of Ōtautahi Christchurch, Cloke and Conradson () agree, describing transitional projects as facilitating community empowerment and contributing to the “re‐coding” of the city that has provided opportunities for participation in projects that foster experiments that contest neoliberal power and work towards creating different worlds.…”
Section: A Diverse Politics Of Disaster Recoverymentioning
confidence: 99%
“…What is highlighted in such an "expanded assemblage of commemoration efforts", as Rico nicely described it, is "affective atmospheres" as Palu Cloke and David Conradson address on a similar occasion, a series of earthquakes that took place in the city of Christchurch, New Zealand, from 2010 to 2011. They focus on discussing how artists and other members of the community affectively engage with each other in order to generate shared senses of being together, which would challenge those who tend to consider post-disaster recovery simply as a "material and measurable" project [9]. In the meantime, endeavors of generating affective atmospheres become more important in Asian countries such as Japan, China, and South Korea where "materiality is [fundamentally] impermanent" (i.e., heritage structures constructed from wood that is highly susceptible to fire) [10,11].…”
Section: Introductionmentioning
confidence: 99%